(untitled) (Képzés és Gyakorlat : Neveléstudományi folyóirat, 2021)
The social changes, which happened in the second half of the 20th century and they have still been happening now, significantly influence the performance of the parental role. For this reason, it is natural that these changes in social conditions have an impact on the educational acting of parents. Family is part of a broader social context with many social connections and relationships. Thus, factors of the broader social environment at the micro-, meso-, exo-, and macro environment levels influence the parental role. In addition, different life and transactional experiences (developmental, situational) mo- dify the parental role and the relationship between family and environment. The article aims to clarify the determinants of the current family role, today`s form of relationships between parents and children, and the changing patterns of the mutual relationship between parents. The article also focuses on parents` tendency to have a more liberal attitude to their children. It points to parents over-protecti- veness and tendency to transfer the responsibility for education to school and educational institutions.